ORGANIZATIONAL AND PEDAGOGICAL CONDITIONS FOR DEVELOPMENT OF RESEARCH COMPETENCY OF FUTURE PHYSICS TEACHERS AT LABORATORY LESSONS - Akzholova А.А (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article covers the organizational and pedagogical conditions for the development of research competence of students in laboratory classes. It provides the methodology of the educational research and the requirements for the presentation of the obtained results, as well as the organization of the activities of the teacher and students in laboratory classes. Also it contains the stages of the educational research at the empirical level, where the objectives of the development of research competence are the orientation of the educational activity to understand and recognize the professional significance of research competence, as well as attracting students to the research activities of the department, aimed at consciously mastering the basic knowledge and skills in the field of scientific research. The characteristic of students’ research competence is given, as the competencies are formed performing laboratory work.